Total flavonoids from Abelmoschus manihot (L.) improve diabetes nephropathy by regulating the gut–kidney axis - Yu, Hongmei; Liu, Yuanxin; Gu, Harvest F.; Tang, Wei; Li, Nan (Frontiers in Medicine, 2026)
BackgroundA recent clinical study demonstrated that Huangkui capsule (with its bioactive constituents being total flavones extracted from Abelmoschus manihot (L.), TFA) combined with irbesartan provides effective therapy for type 2 diabetes (T2D) patients with diabetic nephropathy (DN).ObjectiveThis study aimed to elucidate the therapeutic mechanisms of TFA in DN through the modulation of the gut–kidney axis.MethodsThe db/db mice were administered TFA, irbesartan, or vehicle. Urinary albumin-creatinine ratio (UACR) was measured by the enzyme-linked immunosorbent assay (ELISA). Intestinal bacterial composition was analyzed using 16S rRNA sequencing. Serum metabolites were quantified via LC-ESI-MS/MS. Kidney transcriptomics were assessed using Illumina platform-based RNA sequencing.ResultsAdministration of TFA reduced the UACR in db/db mice and significantly altered intestinal flora composition. Specifically, TFA elevated the abundance of Dietzia, Faecium, Streptococcus, and Blautia while reducing Bacteroidetes, Firmicutes, Enterobacteriaceae, Rikenellaceae, Fusivibrio, and Treponema. In serum metabolomic analysis, TFA increased the levels of quercetin 3-glucuronide and n-cinnamyl glycine but decreased cortisol concentrations. Concurrently, renal transcriptomics revealed the downregulation of key genes, including retnlg, ngp, mpo, camp, ctsg, elane, s100a8, s100a9, trem1, and mmp7, which primarily function in pathways related to neutrophil extracellular trap formation, steroid hormone biosynthesis, and cortisol synthesis/secretion. In contrast, irbesartan treatment did not significantly affect blood pressure or specific renal gene pathways in db/db mice.ConclusionTFA attenuates diabetic nephropathy (DN) progression through pharmacological mechanisms involving three key axes: (1) modulation of intestinal flora composition, (2) regulation of circulating metabolites, and (3) suppression of renal gene activity pathways. These findings highlight the gut–kidney axis as a central therapeutic target for TFA in DN management.